Buddhist Ethics and the way of Living in Daily life: An Analysis of Genital Malfeasances (Kāmesumicchācāra) - et. al., Phrapalad Somchai Damnoen, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Genital malfeasances (kāmesumicchācāra) is the third precept in the Buddhist doctrine means sensual pleasures with another’s the wife or someone’s husband and in the same sutta of the ‘asatdhammadipāyena’, it is referred to having sex with a prohibited person. Rājavoramunī remarks kāmesumicchācāra is demanded to directly and indirectly avoid and forbidden in the five precepts, the eight precepts, and the ten precepts. Remarkably, kāmesumicchācāra acts in Buddhism are compared to the acts of a hungry dog, a hungry vultures, burns by mal-carrying a blazing grass torch, a burning pit, a speedily faded dream, a show-off vanity, a fruit tree risky to be climbed and cut by rogues, a risky meat chopping block, a painful wound pierced by spear or a lance and an endangering snakehead. In this article, the author shall trail through the Principia of ‘genital malfeasances (kāmesumicchācāra)’ with its criteria of violation while inevitably discussing the dilemmas within Buddhist ethics on its avoidances and some alternative perspectives about genital malfeasances (kāmesumicchācāra) through the lenses of some leading scholars.